The Effect Of Bond Time Liquidity and Coupon Bond on the Price of Government Bonds on the Indonesia Stock Exchange Research Period Year 2019-2020 - Bintang Sahala Marpaung; Grinaldo Muhamad (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The company in running its business requires a certain amount of funds to achieve its goals. One of the sources of funds needed is long-term debt, including bonds payable. Bondholders must pay attention to changes in bond prices when investing in bonds. Changes in bond prices are influenced by liquidity, maturity and coupon factors. This study aims to determine the effect of the variables of Liquidity, Maturity Time, and Bond Coupons on the Bond Prices of Companies Listed on the Indonesia Stock Exchange. The period used in this research is 2 years, starting from 2019 to 2020. The population used in this study amounted to 43 series of fixed rate bonds listed on the Indonesia Stock Exchange for the 2019-2020 period. The sample selection technique used purposive sampling method and obtained 27 fixed rate bonds which were used as samples. Technical analysis of the data used multiple linear regression. Based on the results of data analysis, partially Liquidity has an effect on Bond Prices, Maturity Period has a negative and significant effect on Bond Prices, and Bond Coupons have a negative and significant effect on Bond Prices. The results of the multiple regression analysis show that the regression model can be used to predict bond prices as evidenced by the significance value of F of 0.000. Adjusted R-Square value of 0.400 indicates that the ability of the independent variable in explaining the variation of the dependent variable is 40%, and the remaining 60% is explained by other variables outside the research model.